Reversión sexual en tilapias con hormona 17alfa metiltestosterona a diferentes dosis 40-60-80 mg/kg. de alimento en tena sector Uglopamba - Montoya Toapanta, Darwin Xavier (2014)
The present investigation was made, in the Province of Napo, Tena Corner, to an altitude of 518 m.s.n.m. Temperature average 25ºc, relative Humidity 90%, Precipitation: 4000 to 5000 m.m. annual in. The made type of investigation is descriptive, since the study I focus specially to the direct observation of the morphologic characters of the fish to which the genital pores of tila talk about pías. The investigation consisted of proving hormone 17 metil alpha testosterone to different doses (40, 60, 80 mg), like method to produce sexual reversion, applying jointly with the food, for the design of the investigation I am elaborated 3 treatments and a group witness, conformed percent alevines of tilapia of 3 days of age....